The mechanical properties of microwave sewage sludge ash (MSSA) as partial cement replacement in concrete - Tan, Chin Giap (2016)
Rapid urbanization in the developing country leads to prosper of construction sector due to the demand of house, building and infrastructure with the increasing urban population. Hence, cement is highly demand in any construction project. Non-renewable natural resources such as limestone, clay, coal, petroleum, natural gas and fuel oil are consumed in the production of cement will be depleted eventually. Huge quantities of sewage sludge being produced every year and needed to be disposed. Solid waste disposal had come into discussion for years to resolve the space limitation in landfills. An alternative method of sewage sludge disposal is to utilize it as one of the construction materials. Despite of incineration method to reduce the quantities of sewage sludge, microwave heating which is more efficient in term of time and energy consumption is used in this research. Microwave Sewage sludge ash (MSSA) is proposed as partial cement replacement in concrete. 0%, 5%, 10% and 15% MSSA which were heated at medium and medium-high temperature are used in this research. Compressive strength, flexural strength, UPV and XRD were performed. The mechanical properties of MSSA concrete were compared among each other and conventional concrete G30. The results showed that 5% MSSA which was microwave heated at medium-high temperature is the optimum percentage replacement in concrete.